Engineering Method for Calculating of an Axial Valve Separator With an External Location of the Locking Part - Kapranova, Anna; Neklyudov, Sergey; Lebedev, Anton; Meltser, Alexander; Voronin, Dmitriy (Frontiers in Energy Research, 2020)
Proposed a block diagram of the calculation of the axial valve separator. The required valve flow capacity is taken into account. The results of stochastic modeling of the hydrodynamic cavitation are the basis. An example of the calculation of the axial valve separator is made.